Menjelajahi minat remaja awal dalam partisipasi ekstrakurikuler futsal - Qorry Armen Gemael; Zihan Novita Sari (Universitas Nusantara PGRI Kediri, 2025)
The degree of student involvement in every emerging sport shows how well the institution promotes physical exercise and teamwork. High participation also suggests that extracurricular activities are interesting and sensitive to student needs and preferences. This study will examine the elements that influence student involvement in futsal extracurricular activities. This study uses a quantitative descriptive approach with a survey design. The sampling technique used is simple random sampling, with 79 students actively participating in futsal training sessions at a junior high school in an urban area with high student participation in sports. A standardized questionnaire with Likert scale items is used to collect data on various characteristics of interest in sports, including enjoyment, motivation, peer influence, and perceived benefits of futsal. Education experts evaluated the instruments to ensure they were relevant and clear. Data were analyzed using descriptive statistical methods, focusing on percentage distributions to identify respondent interest level patterns. The findings indicate that students' enthusiasm for futsal extracurricular activities is generally low. Only 38 students (29.64%) showed strong interest, while the rest showed moderate to low enthusiasm. This data suggests that, despite futsal's popularity, underlying motivational or contextual barriers prevent widespread participation. Finally, the low level of interest among children indicates that extracurricular sports activities should be promoted and activated in schools in different ways. This study helps develop more successful engagement tactics targeted at students' interests and needs, supporting the overall goal of creating a more active and health-conscious school environment.